The certified Six Sigma yellow belt handbook - Ramu, Govindarajan (ASQ Quality Press, 2016)
"This reference manual is designed to help both those interested in passing the exam for ASQ's Certified Six Sigma Yellow Belt (CSSYB) and those who want a handy reference to the appropriate materials needed for successful Six Sigma projects. It is intended to be a reference for both beginners in Six Sigma and those who are already knowledgeable about process improvement and variation reduction.The primary layout of the handbook follows the Body of Knowledge (BoK) for the CSSYB released in 2015. The author has utilized feedback from Six Sigma practitioners and knowledge gained through helping others prepare for exams to create a handbook that will be beneficial to anyone seeking to pass not only the CSSYB exam but also other Six Sigma exams. In addition to the primary text, the handbook contains numerous appendixes, a comprehensive list of abbreviations, and a CD-ROM with practice exam questions, recorded webinars, and several useful publications. Each chapter includes essay-type questions to test the comprehension of students using this book at colleges and universities. Six Sigma trainers for organizations may find this additional feature useful, as they want their trainees (staff) to not only pass ASQ's Six Sigma exams but have a comprehensive understanding of the Body of Knowledge that will allow them to support real Six Sigma projects in their roles"--